PEG reimplantation after Buried Bumper Syndrome: a case report. - Fornaroli, Fabiola; Gualandi, Noemi; Vincenzi, Francesca; Laghi, Luigi; de'Angelis, Gian Luigi; Gaiani, Federica (Acta Biomedica Atenei Parmensis, 2022)
Percutaneous endoscopic gastrostomy (PEG) is the method of choice to provide long-term enteral nutrition for patients with impossibility to be fed orally. Although it is considered a routine and safe procedure, potential complications exist, which are generally classified into three major categories: endoscopic technical difficulties, PEG procedure-related complications and late complications associated with PEG tube use, such as buried bumper syndrome (BBS). BBS is a life-threatening complication, occurring in 0.3% to 2.5% of cases. Additional complications related to BBS may present, such as wound infection, peritonitis, and necrotizing fasciitis. Once resolved the acute complication, an adequate feeding method should be prompted for the patient, among whom PEG remains of choice. After tissue inflammation, fibrosis may prevent a standard endoscopic procedure for the new implantation, therefore endoscopists should modulate procedures to obtain successful and safe results. A combined surgical- and endoscopic strategy could resolve implantation difficulties ensuring a safe and simple procedure.We present here a case of BBS complicated with abdominal wall cellulitis in a paraplegic 35-year-old-man who was admitted to our hospital.